Hot electron relaxation dynamics in semiconductors: assessing the strength of the electron–phonon coupling from the theoretical and experimental viewpoints. (7th August 2018) - Sjakste, J; Tanimura, K; Barbarino, G; Perfetti, L; Vast, N
Abstract: The rapid development of the computational methods based on density functional theory, on the one hand, and of time-, energy-, and momentum-resolved spectroscopy, on the other hand, allows today an unprecedently detailed insight into the processes governing hot-electron relaxation dynamics, and, in particular, into the role of the electron–phonon coupling. Instead of focusing on the development of a particular method, theoretical or experimental, this review aims to treat the progress in the understanding of the electron–phonon coupling which can be gained from both, on the basis of recently obtained results. We start by defining several regimes of hot electron relaxation via electron–phonon coupling, with respect to the electron excitation energy. We distinguish between energy and momentum relaxation of hot electrons, and summarize, for several semiconductors of the IV and III–V groups, the orders of magnitude of different relaxation times in different regimes, on the basis of known experimental and numerical data. Momentum relaxation times of hot electrons become very short around 1 eV above the bottom of the conduction band, and such ultrafast relaxation mechanisms are measurable only in the most recent pump-probe experiments. Then, we give an overview of the recent progress in the experimental techniques allowing to obtain detailed information on the hot-electron relaxation dynamics, with the main focus on time-, energy-, and momentum-resolved photoemission experiments. The particularities of the experimental approach developed by one of us, which allows to capture time-, energy-, and momentum-resolved hot-electron distributions, as well as to measure momentum relaxation times of the order of 10 fs, are discussed. We further discuss the main advances in the calculation of the electron–phonon scattering times from first principles over the past ten years, in semiconducting materials. Ab initio techniques and efficient interpolation methods provide the possibility to calculate electron–phonon scattering times with high precision at reasonable numerical cost. We highlight the methods of analysis of the obtained numerical results, which allow to give insight into the details of the electron–phonon scattering mechanisms. Finally, we discuss the concept of hot electron ensemble which has been proposed recently to describe the hot-electron relaxation dynamics in GaAs, the applicability of this concept to other materials, and its limitations. We also mention some open problems.